2016
DOI: 10.1902/jop.2016.150602
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis Lipopolysaccharide Stimulation of Vascular Smooth Muscle Cells Activates Proliferation and Calcification

Abstract: Pg-LPS can stimulate VSMC calcification, which results in vascular calcification, further proving the precise relationship between periodontitis and vascular calcification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Recently, further study that investigates the relationship between periodontitis and cardiovascular diseases has focused on the effect of P. gingivalis infection on the pathophysiology of VSMCs. The evidence from these in vitro and in vivo studies showed that the P. gingivalis infection of VSMCs and the stimulation of VSMCs with P. gingivalis ‐derived components regulate the pro‐thrombotic response, proliferation, and calcification of VSMCs (Hokamura et al, ; Liu et al, ; Olsen & Progulske‐Fox, ; Reyes et al, ; Yang et al, ). Moreover, those P. gingivalis ‐derived components include the fimbriae, capsule, and outer vesicles of P. gingivalis and P. gingivalis ‐secreted LPS, haemagglutinins, and proteases (gingipains) (Liu et al, ; Yang et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, further study that investigates the relationship between periodontitis and cardiovascular diseases has focused on the effect of P. gingivalis infection on the pathophysiology of VSMCs. The evidence from these in vitro and in vivo studies showed that the P. gingivalis infection of VSMCs and the stimulation of VSMCs with P. gingivalis ‐derived components regulate the pro‐thrombotic response, proliferation, and calcification of VSMCs (Hokamura et al, ; Liu et al, ; Olsen & Progulske‐Fox, ; Reyes et al, ; Yang et al, ). Moreover, those P. gingivalis ‐derived components include the fimbriae, capsule, and outer vesicles of P. gingivalis and P. gingivalis ‐secreted LPS, haemagglutinins, and proteases (gingipains) (Liu et al, ; Yang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…SMC calcification, a form of mineralization, was determined by using the Alizarin Red S (ARS) stain, which was used to detect the calcium deposition (Liu et al, ; Yang et al, ). HGPg‐infected HASMCs were fixed with 10% formaldehyde and then stained with ARS (40 mM).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifth, vascular calcification is a prominent feature of AS. P. gingivalis LPS can stimulate the proliferation and calcification of SMCs, resulting in vascular calcification [ 42 ]. P. gingivalis OMVs were also reported to promote vascular SMC calcification through ERK1/2-RUNX2 [ 43 ].…”
Section: Cardiologymentioning
confidence: 99%
“…P. gingivalis is a gram negative bacterium. Experimental results indicate that P. gingivalis DNA and P. gingivalis endotoxin (LPS) can be found in a therogenic plaque in CVD patients with periodontal disease (Liu et al, ). Lee et al () indicated that P. gingivalis damages H9c2 cardiomyoblasts by inducing hypertrophy markers and activating the MMP 9 fibrosis marker.…”
Section: Introductionmentioning
confidence: 99%